On-Orbit Real-Time Signal Processing for Spaceborne Digital Beamforming Scatterometer - Yongqing Liu; Peng Liu; Risheng Yun; Te Wang; Xiangkun Zhang (IEEE Access)
Sea Surface Salinity (SSS) is a crucial parameter influencing ocean circulation and the global water cycle in global climate monitoring and oceanographic research. However, remote sensing of SSS is challenged by the impact of sea surface roughness on microwave radiation measurements. To enhance measurement accuracy, the Ocean 4A satellite is equipped with a digital beamforming scatterometer integrated with advanced active and passive microwave remote sensing instruments. This system provides timely sea surface roughness information through co-frequency observations, enabling real-time correction of radiometric measurement errors. In this study, we conduct an in-depth analysis of the on-orbit real-time signal processing technology of the spaceborne digital beamforming scatterometer, covering system architecture, real-time signal processing algorithms, and software optimization. The developed real-time signal processing algorithms demonstrate excellent performance, achieving high accuracy and reliability in data acquisition. Results from point target tests using a combined echo simulator and airborne calibration and validation confirm the effectiveness of the proposed methods. These findings lay a solid foundation for high-precision SSS measurements and showcase the potential of the Ocean 4A scatterometer in enhancing global climate monitoring capabilities.